Weed Control in Pinus Plantations I. Effect of Herbicides on Metabolism of Weeds - Soni, Prafulla (Indian Forester, 1977)
Present study has been undertaken to control the weeds Pinus plantations located in New Forest, Dehra Dun. The effect of application of various herbicides on the net gross primary production of wood has been evaluated using leaf disc method. From the results obtained has been concluded that applicatlon herbicides in plantations reduced the rate of photosynthesis and thus the net production considerably which ulthmately resulted in either the death of weeds or the growth was significantly reduced.